SEMUA ILMU ADA DALAM AL-QURâ€™AN: Telaah Pemikiran al-SuyÅ«thiy dalam al-ItqÄn fÄ« â€˜UlÅ«m al-Qurâ€™an - Farihin, Hibbi (IAIN Tulungagung, 2016)
One of the chapters (naw?u?) which was discussed interestingly in al-Itq?n f? ?Ul?mal-Qur??n by Jal?l al-D?n al-Suy?thiy (d. 911 H) was the 65th chapter, namely f? al-?Ul?m al-Mustanbathah min al-Qur?an (the sciences that was based on the al-Qur'an). Among those who agree, they will show some evidence for the al-Suy?thiy thesis. While that does not agree, confirming the position of the al-Qur'an that is limited by time and space. This paper describes a number of data of al-Suy?thiy writting about his views on this matter. Hopefully, after understanding the arguments of al-Suy?thiy, every readers can determine their positions on that view.Keywords: Sciences resting on al-Qur?an, al-Suy?thiy, the position of the readers